Not Practicing What You Preach: Religion and Incongruence Between Pornography Beliefs and Usage. Issue 3 (24th March 2018) - Perry, Samuel L.
Abstract : Religious Americans, and conservative Protestants in particular, have historically been the most ardent opponents of pornography's production, dissemination, and use. Yet while religiously committed and theologically conservative Americans are generally less likely to view pornography than others, the difference is often not as great or consistent as one might suppose given their strong moral stance. Drawing on insights from religious incongruence theory, this study considered whether religious commitment and theological conservatism predicted a greater incongruence between what Americans say they believe about pornography morally and whether they actually watch it. Data are taken from the nationally representative 2006 Portraits of American Life Study ( N  = 2, 279). Analyses show that greater religious service attendance and prayer frequency are predictive of American men (not women) affirming that viewing pornography is "always morally wrong" while still viewing it in the previous year. Evangelicalism and other sectarian Protestantism are also the religious traditions most likely to believe pornography is always morally wrong while also viewing it. Findings ultimately suggest that religious commitment and affiliation with theological conservatism may influence Americans (primarily men) to oppose pornography more strongly in principle than reflected in actual practice. Data limitations and implications for future research are discussed.